Overcrowding in prisons: Health and legal implications - Eva Nudd; Maha Aon; Kalliopi Kambanella; Marie Brasholt (Torture)
Introduction: Prison overcrowding can be defined in different ways, and no universal definition exists. More than 120 countries report prison occupancy rates above their own capacity. This paper provides an overview of legal and health implications of overcrowding, analyses potential causes, and provides examples of how different countries utilised non-custodial measures to reduce overcrowding to disseminate good practices as inspiration for other contexts. Methods: Desk study based on literature searches in medical (Pubmed and Medline) and legal sources, including Google Scholar on legal opinions, Global Lex and decisions of UN treaty bodies and regional human rights mechanisms supplemented by online searches for grey literature. In addition, examples from other countries were sought to corroborate and illustrate the points made. Results: A range of international standards exist that provide for the conditions and treatment of people in prisons to prevent prison overcrowding and protect them from its consequences. Nonetheless, overcrowding is persistent across many countries. It is often associated with violations of human rights, including, among others, the right to be free from torture and ill-treatment, the right to health, and the right to liberty and security. The underlying factors contributing to overcrowding vary and include, among others, overuse of imprisonment, excessive use of pre-trial detention, lack of access to a lawyer and underutilisation of non-custodial measures as an alternative to detention. Non-custodial measures can be applied throughout the criminal justice process, and some countries have successfully managed to reduce their prison populations by implementing such measures. Discussion: Overcrowding affects many aspects of prison life, impeding the provision of a humane and rehabilitative environment. Beyond the harm caused to persons in prisons, this may negatively impact society at large in terms of security, public health, and economy. Political will is essential in reducing prison overcrowding.